An investigation of cyanide-based heap leaching for extracting precious metals from Platreef ore - Mwase, James Malumbo (Centre for Bioprocess Engineering Research, 2018)
Cyanide heap leaching had been proposed as an alternative to the classic crush-mill-loatsmelt-refine route for processing platinum group metals (PGMs) from the Platreef ore body. Overall the process includes two stages of leaching. The first stage involves the thermophile bioleaching of the base metal (BM) sulphide minerals and acts as a form of pre-treatment to oxidise sulphur compounds and recovery valuable metals such as Cu, Ni and Co. The second stage focuses on cyanide-based heap leaching for the recovery of precious metals (PGMs +gold) from the solid residue of the first stage. Exploration and optimisation of this second stage in the context of a whole ore Platreef material is the focus of the present study. The first part of the study used a series of laboratory tests simulating heap leaching, conducted on coarse ore. The initial tests showed high recoveries of base metals (Cu, Ni and Co) could be achieved in a pre-treatment bioleach process, while in the second stage cyanide leach high levels of Pd and Au were extracted, but only 58% of the Pt after 60 days from the whole ore. It was observed that during the 60 day leaching period the rate of Pt leaching decreased considerably after 35 days. From the trajectory of the Pt leach curve from the 35 day mark onwards, it was observed that the leaching would not cease even after 60 days but would likely proceed but at that slow pace which indicated further Pt extraction would not be commercially viable in the long run. Mineralogical analysis has indicated that a significant component of the Pt in the ore is in the form a mineral sperrylite (PtAs2), which appears to leach slowly in cyanide as compared to other mineral forms such as certain tellurides and sulphides in the ore. Subsequently, efforts were made to investigate methods to improve the second stage leach process, in terms of Pt leaching from sperrylite, through further work on a pure mineral sample. The key focus was on finding a suitable oxidant that can be used in cyanide solutions, from among air, oxygen and ferricyanide, to facilitate the dissolution. Various tests using sperrylite mineral samples micronized to 5 μm in batch stirred tank reactors (BSTR) at 50°C were conducted. It was found that a combination of ferricyanide with cyanide extracted as much as 16 times more Pt than tests using only cyanide. The presence of air or pure oxygen did not contribute significantly to the amount of Pt leached in this system and made no difference at all in the leach tests using only cyanide. Further bench-scale studies focused on characterising the leaching mechanism of sperrylite in cyanide-ferricyanide solutions. It was found that the reaction, after proceeding at appreciable rates initially, tended to cease after 1 day, indicating some form of surface passivation, tentatively related to some form of solution equilibrium being achieved. However after re-leaching the sample with fresh solution, the Pt dissolution improved tremendously. This was further investigated in continuous leaching of a sample of the mineral using a small bed of sperrylite fixed in mini-columns. The results from the minicolumns showed the same leaching pattern as the experiments using BSTRs. It was eventually revealed that a suitable wash of the sperrylite sample using water removes the inhibiting layer and facilitates further and improved leaching. Unlike the cyanide-only system where the passivation was attributed to As build-up at the surface, in the cyanide-ferricyanide system it was attributed to adsorption of unknown reaction products on the mineral surface. Residual samples from batch leach experiments were analysed using X-ray photoelectron spectroscopy and showed samples from the cyanide-ferricyanide tests had less As on the surface than the untreated sample and the sample leached in cyanide. To some degree this supported the hypothesis that Pt leaching is eventually hindered by As passivation in a cyanide system. The presence of ferricyanide serves to oxidise As and thereby release more Pt in solution. Additionally, electrochemical techniques using a sperrylite electrode were employed to further understand the redox reaction under varying oxidation conditions. While the tests indicated a weak current under mildly oxidising conditions in cyanide solutions, this became rapidly limiting at potentials expected in a ferricyanide solution, indicating a form of surface passivation. An attempt was made to determine the number of electrons transferred during Pt dissolution to indicate the primary reaction mechanism through a long-term test held at constant potential, but dissolution rates were too small to be conclusive. Hence the study has shown that the cyanide-based heap leaching of PGMs from Platreef type ores is feasible in principle, but the dissolution of PtAs2 remains limited. While the study has given valuable pointers to understanding this observation, the conclusion is that PtAs2 is refractory in the given context and further development of this process remains promising through further investigation into the use of the cyanide-ferricyanide combination.